Non-Volatile Metabolic Profiling and Regulatory Network Analysis in Fresh Shoots of Tea Plant and Its Wild Relatives - Jiang, Chen-Kai; Liu, Zhi-Long; Li, Xuan-Ye; Ercisli, Sezai; Ma, Jian-Qiang; Chen, Liang (Frontiers in Plant Science, 2021)
There are numerous non-volatile metabolites in fresh shoots of tea plant. In fact, we know little about the complex relationship among the content of these metabolites with expression level of genes and themselves. Therefore, non-volatile metabolites of 68 accession tea plants were detected and identified using untargeted metabolomics. The tea accessions were divided into three groups as the result of principal component analysis based on the relative content of metabolites. And there were differences of variabilities between the primary and secondary metabolites. Furthermore, correlations of gene-gene, gene-metabolite, and metabolite-metabolite were conducted based on PCC value. The current study offers several significant insights into co-current network of genes and metabolites in global genetic background and thus it is useful to provide lights into regulatory relationship of genetic basis for predominant metabolites in fresh tea shoots.